Compulsory psychiatric admissions in the canton of Basel-Stadt between September 2013 and April 2022: Analysis of the cantonal database of the Health Department of Basel-Stadt. (June 2023) - Schneider, Michael; Back, Moritz; Krückl, Jana S; Moeller, Julian; Lang, Undine E; Huber, Christian G
Background: According to federal and cantonal law, persons with an acute mental illness can be admitted to a psychiatric hospital or another suitable institution against their will, when other therapeutic options are not available or have been exhausted. In the canton of Basel-Stadt, this is the responsibility of public health officers employed by the division of Social Medicine of the cantonal Health Department. Aims: This study aims to elucidate which factors influence the decision-making of public health officers regarding compulsory admissions over the period from September 2013 to April 2022 in the canton of Basel-Stadt. Method: Leveraging comprehensive clinical data from the health department of the canton Basel-Stadt ( N  = 5, ′550), we estimated a mixed effects logistic regression model to identify factors contributing to the decision of public-health officers to compulsorily admit patients, while controlling for potential clustering effects among public health officers. Results: The risk for compulsory admissions was most strongly predicted by the presence of potential self-harm. In comparison, while being a strong predictor, potential harm to others played a considerably lesser role. Furthermore, psychiatric syndrome, previous compulsory admissions, and the specific context of evaluation were significant predictors. Finally, we found no meaningful personal bias among public health officers. Conclusion: The results suggest that public health officers' decision-making regarding compulsory admissions focuses on preventing self-harm and, to a lesser degree, harm to others. This indicates that such measures are only used as a measure of last resort, which is in line with current evidence regarding the detrimental effects of compulsory measures on treatment outcomes in psychiatry. Our findings suggest that all relevant stakeholders, including the police, share this perspective. Decision-making regarding compulsory admissions was mostly free of personal biases, suggesting adherence to shared professional standards by public health officers.